2003
DOI: 10.1038/sj.ejhg.5200935
|View full text |Cite|
|
Sign up to set email alerts
|

Spectrum of mutations in PTPN11 and genotype–phenotype correlation in 96 patients with Noonan syndrome and five patients with cardio-facio-cutaneous syndrome

Abstract: Noonan syndrome (NS) is a relatively common, but genetically heterogeneous autosomal dominant malformation syndrome. Characteristic features are proportionate short stature, dysmorphic face, and congenital heart defects. Only recently, a gene involved in NS could be identified. It encodes the nonreceptor protein tyrosine phosphatase SHP-2, which is an important molecule in several intracellular signal transduction pathways that control diverse developmental processes, most importantly cardiac semilunar valvulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
110
1
18

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 22 publications
12
110
1
18
Order By: Relevance
“…The mutations and clinical features of four of these fetuses have also been described elsewhere; case 1 has been described by Bakker et al 24 and cases 9, 12 and 13 have been described by Houweling et al 27 Nine fetuses had a de novo mutation in PTPN11, three in RAF1 and one in KRAS. Eight of the 12 different mutations detected in this study have been described earlier in postnatally identified NS patients: PTPN11; c.174C4G (p.(Asn58Lys)), 28 c.182A4G (p.(Asp61Gly)), 4 c.184T4G (p.(Tyr62Asp)), 5 c.205G4C (p.(Glu69Gln)), 28 c,417G4C (p.(Glu139Asp)), 5 and c.854T4C (p.(Phe285Ser)), 5 RAF1 c.770C4T (p.(Ser257Leu)), 10 and KRAS c.173C4T (p.(Thr58Ile)). 6 One mutation has been previously described in a patient with the clinical diagnosis of LEOPARD syndrome: PTPN11 (c.1381G4A, p.(Ala461Thr)).…”
Section: Diagnostic Study Groupmentioning
confidence: 54%
“…The mutations and clinical features of four of these fetuses have also been described elsewhere; case 1 has been described by Bakker et al 24 and cases 9, 12 and 13 have been described by Houweling et al 27 Nine fetuses had a de novo mutation in PTPN11, three in RAF1 and one in KRAS. Eight of the 12 different mutations detected in this study have been described earlier in postnatally identified NS patients: PTPN11; c.174C4G (p.(Asn58Lys)), 28 c.182A4G (p.(Asp61Gly)), 4 c.184T4G (p.(Tyr62Asp)), 5 c.205G4C (p.(Glu69Gln)), 28 c,417G4C (p.(Glu139Asp)), 5 and c.854T4C (p.(Phe285Ser)), 5 RAF1 c.770C4T (p.(Ser257Leu)), 10 and KRAS c.173C4T (p.(Thr58Ile)). 6 One mutation has been previously described in a patient with the clinical diagnosis of LEOPARD syndrome: PTPN11 (c.1381G4A, p.(Ala461Thr)).…”
Section: Diagnostic Study Groupmentioning
confidence: 54%
“…A role for SHP-2 in vertebrate heart development was demonstrated through the observation that missense mutations are often associated with Noonan syndrome, one of the most common human congenital heart diseases that leads to a number of cardiac developmental abnormalities, including atrial septal defects, ventricular septal defects, pulmonary stenosis and hypertrophic cardiomyopathy (Kosaki et al, 2002;Maheshwari et al, 2002;Noonan, 1968;Noonan, 1994;Tartaglia et al, 2002;Tartaglia et al, 2001). Interestingly, patients with acute myelogenous leukemia (AML), acute lymphoblastic leukemia (ALL), juvenile myelomonocytic leukemia (JMML) and LEOPARD syndrome frequently carry a second, somatically introduced subset of missense mutations in SHP-2 (Bentires- Alj et al, 2004;Digilio et al, 2002;Kratz et al, 2005;Legius et al, 2002;Loh et al, 2004;Musante et al, 2003;Tartaglia et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Different genes of the RAS/MAPK signaling pathway are responsible for NS (Table 1) (3)(4)(5)(6)(7)(8)(9)(10)(11). Mutation in the PTPN11, SOS1, RAF1 and KRAS genes, usually leading to a gain-of-function, is found in approximately 70% of NS (12) cases.…”
mentioning
confidence: 99%